Perencanaan Instalasi Pengolahan Air Limbah (IPAL) Kawasan Industri Tuban - Dinda Diera Kofuji (Fakultas Teknik, 2025)
Tuban Industrial Estate is one of the industrial zones located in East Java that implements environmental control and management through the provision of an on-site Wastewater Treatment Plant (WWTP). The estate currently operates a WWTP with a capacity of 150 m³/day and plans to expand its capacity to 10,000 m³/day using a new land area. This study aims to design a WWTP for the Tuban Industrial Estate with a capacity of 10,000 m³/day, focusing on the removal of BOD, COD, TSS, pH, and ammonia parameters. The estate applies standard inlet quality criteria to equalize the wastewater characteristics from all tenants, facilitating more efficient treatment processes. The planned treatment units include physical, chemical, and biological processes. Wastewater is conveyed through collection channels and passes through a bar screen with a rectangular shape and sharp edges to remove solid materials. A collection sump measuring 7 m x 3.5 m x 2.75 m temporarily stores the wastewater before it enters the aerated grit chamber (7.5 m x 2.5 m x 2.8 m). The Dissolved Air Flotation (DAF) system, operating at an P of 300 kPa, assists in removing suspended solids. Wastewater is then homogenized in an equalization tank with a detention time of 30 minutes before entering the biological treatment unit. The Moving-bed Biofilm Sequencing Batch Reactor (MBSBR) is applied as the biological treatment, utilizing biofilm in a batch system for optimal performance, with a unit size of 11 m x 5.5 m x 3 m. The biologically treated effluent is disinfected using a chlorine solution before being discharged into the receiving water body. Sludge generated from the treatment process is collected in a Sludge Drying Tank to reduce its moisture content, followed by dewatering using a press and temporary storage in a hazardous waste storage facility (TPS Limbah B3).
Reaploud Repository February_Hasyim
Keywords: Aerated Grit Chamber; Dissolved Air Flotation (DAF); Industrial Estate; Moving-bed Biofilm Sequencing Batch Reactor (MBSBR); Sludge Drying Tank.